1979
DOI: 10.1021/bk-1979-0112.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Parameters and Methods in Quantitative Structure-Activity Relationships

Abstract: In studies of quantitative structure activity relationships (QSAR), the relative potencies of a series of drugs are subjected to analysis with the hope that biological potency will be described by a mathematical equation. QSAR is an actuarial or statistical method in which only objective data are used with no intrusion of models or mechanistic hypotheses. The equation that is obtained not only accounts for the relative potencies of the compounds, but from it are deduced predictions of the potencies of untested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The Taft steric substituent constant is of interest in its own right and has been useful in biological QSAR [Osman et al, 1979;Hansch, 19781. In fact, the problems associated with the three-dimensional character of molecules is one of the more underdeveloped areas of QSAR work.…”
Section: Steric Parametersmentioning
confidence: 99%
“…The Taft steric substituent constant is of interest in its own right and has been useful in biological QSAR [Osman et al, 1979;Hansch, 19781. In fact, the problems associated with the three-dimensional character of molecules is one of the more underdeveloped areas of QSAR work.…”
Section: Steric Parametersmentioning
confidence: 99%
“…However, these reactivity criteria are often artificially constructed parameters with no obvious formal relationship to recognition and activity, whereas the electrostatic potential generated by a molecule is an experimentally observable quantity from high energy electron scattering (46) For example, in a series of studies on the molecular determinants for recognition and activity at the receptors of the neurotransmitter serotonin (5-hydroxytryptamine; 5-HT) a major recognition element is the electrostatic potential (24,48). We showed that the MEP over the indole portion of 5-HT congeners, and of congeners of lysergic acid diethylamide (LSD), has a characteristic directionality that can be represented by an electrostatic orientation vector.…”
Section: C12mentioning
confidence: 99%
“…If, however, the toxicity of the molecule is related to its ability to act as a whole, e.g., by intercalation,then a more relevant representation of the MEP would be on a surface around the molecule. These two simple examples illustrate the manner in which MEP maps can be used, and have been used in the past [e.g., see (57) for localized values, and (24,47,48) for values on surfaces] to obtain information about the reactivity characteristics of drugs in relation to specific mechanistic propositions. As a screening procedure, however, this approach is strongly dependent on information about the mechanism and is therefore less general than required for a selection of MEP characteristics relevant to broadly defined toxicity.…”
Section: New Approaches To the Calculation Of Mep And The Analysis Ofmentioning
confidence: 99%
See 2 more Smart Citations